The Impact of Firm-specific and Macroeconomic Factors on the Share Price of Nepali Commercial Banks - Timalsina , Dhanishor (The Management Review, 2026)
This study attempts to test the impact of certain firm-related variables (i.e., EPS, DPS, P/E ratio, firm size, and ROA) along with macroeconomic variables (i.e., GDP growth, inflation rate, and interest rate) on the stock price of Nepali commercial banks. The study is conducted through the application of panel data of thirteen listed banks for the period of 2011/12 to 2023/24 applying regression analysis supplemented by descriptive and correlation analyses. The findings reveal that EPS, DPS, P/E ratio, firm size, and inflation have a positive effect on the price of shares, whereas interest rate has a negative effect on the price of shares. On the contrary, ROA and GDP growth rate do not have a significant effect on the price of shares. This study highlights the significance of financial indicators, stable dividend policies, and interest rate considerations for investors, managers, policymakers, and future researchers by providing updated evidence from Nepal demonstrating that both firm-specific and macroeconomic factors influence share prices.